Bejalai: a YouTube journey / Joshua Kedam Edmund and Zuraidah Sumery - Edmund, Joshua Kedam; Sumery, Zuraidah (Academy of Language Studies, 2023)
Bejalai is a YouTube based content creation channel that guides students to travel to their universities. It is created to guide students that have never experienced travelling by public transportations especially those from the Island of Borneo. With the creation of Bejalai, the students could travel to their universities without worrying that they might experience trouble travelling. Bejalai aims to help students to travel to their respective universities from Terminal Bersepadu Selatan, starting from the guide to travel to UiTM Segamat. Due to the length of the videos and the ability to reach out to students easier, the researcher has picked YouTube as the main platform to execute the experience. Through this YouTube journey, it is hoped that it could accumulate intriguing experiences for those who are in need the service. Hence, bejalai has played an important role in preparing the students of what to expect when they travel to unfamiliar places.